Deterioration of shear behavior of corroded reinforced concrete beams. (1st August 2018) - Ye, Zhiwen; Zhang, Weiping; Gu, Xianglin
Highlights: The change of failure modes of RC beams due to corrosion of steel bars were investigated. Effects of corrosion of steel bars on shear behavior were studied. Effects of bond behavior and anchorage of stirrups on shear behavior were studied. Abstract: Steel bars in reinforced concrete (RC) structures may corrode in an aggressive environment, resulting in performance deterioration and premature failure. Stirrups begin to corrode earlier and faster than longitudinal steel bars due to their thinner concrete cover, and the shear strength decreases faster than the flexural strength. This paper presents an experimental investigation into the deterioration mechanism of shear behavior for corroded RC beams, and the prominent influencing parameters on shear behavior. The impressed current method was used to obtain corroded RC beams with different corrosion degrees in stirrups and longitudinal steel bars. Test results indicated that the beam may fail in shear instead of bending as the degrees of stirrup corrosion increases. The more severe the corrosion of stirrups was, the lower the shear strength. However, as the degree of corrosion increased in the longitudinal steel bars, the failure mode could change back to bending failure. The loss of bond strength affected the shear behavior of corroded RC beams, and the shear strength for bonded specimens was larger than unbonded ones. The shear strength decreased in beams with stirrups lacking end anchorages. Stirrups without end anchorages could still contribute to the shear strength if there was a good bond between stirrups and concrete. Otherwise, the stirrups could be ignored. With neither bond strength nor end anchorage, the beam could be treated as a beam without stirrups.